2011
DOI: 10.5209/rev_sjop.2011.v14.n1.35
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Version of the Prospective and Retrospective Memory Questionnaire (PRMQ-S)

Abstract: The concept of prospective memory is relatively recent. Thus, it is necessary to have instruments to assess it, in interaction with retrospective memory. The Prospective and Retrospective Memory Questionnaire (PRMQ; Smith et al., 2000) is an instrument that has been effectively used for assessment in several languages. Nevertheless, there is still no Spanish adaptation. The aim of this study was to translate the PRMQ and obtain information about its psychometric properties. A back translation process was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
3
9
0
1
Order By: Relevance
“…A similar pattern was reported in studies using an exploratory factor analysis (Benites & Gomes, 2007; González-Ramírez & Mendoza-González, 2011). So far, only two studies found satisfactory item loadings for the tripartite model (Crawford et al, 2003; Rönnlund, Mäntylä & Nilsson, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…A similar pattern was reported in studies using an exploratory factor analysis (Benites & Gomes, 2007; González-Ramírez & Mendoza-González, 2011). So far, only two studies found satisfactory item loadings for the tripartite model (Crawford et al, 2003; Rönnlund, Mäntylä & Nilsson, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the construct validity, although the tripartite model was the one with the best fit indices as already found in former investigations (Crawford et al, 2006; Crawford et al, 2003; González-Ramírez & Mendoza-González, 2011; Hsu & Hua, 2011; Piauilino et al, 2010; Rönnlund, Mäntylä & Nilsson, 2008; van der Werf & Vos, 2011), it was also observable that not all the items loaded in the expected factors. A similar pattern was reported in studies using an exploratory factor analysis (Benites & Gomes, 2007; González-Ramírez & Mendoza-González, 2011).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations